Hubungan Kontrol Diri dengan Kebahagiaan Santri Penghafal Al-Qur’an - Widiantoro Widiantoro; Reiza Ekasyahputra Purawigena; Witrin Gamayanti (UIN Sunan Kalijaga, 2017)
As students in college and santri memorizing al-qur’an make them busy and stress, but so many activities make them still happy. They have been memorizing al-qur’an and finishing their assignment from the college, and self-control help students organizing they activities and focus on their task. This research was intended to measure the effect of self-control on happiness. Subject of this study were 115 population and 21 santri only comply with requirement from pesantren located in Bandung. Data collected through questioners, and analyzed using simple regression. The result showed that there was significant effect of self-control on happiness (r=0.642, p=0,002). It means that self-control contribute to their happiness on santri memorizing Al-Qur’an.